Quantifying the peak physical match-play demands of professional soccer substitutes following pitch-entry: assessing contextual influences - Hills, S. P.; Barrett, S.; Thoseby, B.; Kilduff, L. P.; Barwood, M. J.; Radcliffe, J. N.; Cook, C. B.; Russell, M. (Research Quarterly for Exercise and Sport, 2022)
Purpose: To quantify the peak post-pitch-entry physical responses of soccer substitutes while assessing contextual influences. Peak responses may be important performance indicators for substitutes introduced to provide a physical impact.